SEMINAL BREAKTHROUGH IN TACTILE PICTOGRAM DESIGN FOR VISUALLY IMPAIRED IN TRAIN STATION - Fariz Fadhlillah (ULTIMART Jurnal Komunikasi Visual, 2020)
One of the ideal public transportation facilities for the visually impaired in daily activities is trains. To be used at maximum, there is a need for communicative media to support the independence of orientation and mobility for the visually impaired in the train station. The media plays a role in supporting visually impaired individuals to know where they are, where to go, and how to reach the destination. The previous result regarding visually impaired ability to identify pictorial form which is designed with Primadi Tabrani’s ancient visual language semiotic approach shows a great opportunity for a pictogram to be the solution. However, the challenge is how to make the visually impaired person understand the meaning description that has been designed into tactile pictogram by touch. Basic consideration in designing process is the clarity of visual form when being touched, which is influenced by the way the shape is drawn and the tactile height